The balance between deception and adaptation: vasculogenic mimicry as a tumor survival strategy - E. A. Prosekina; V. A. Shapkina; A. E. Karpov; E. Yu. Fedorutseva; A. S. Artemyeva (Успехи молекулярной онкологии)
Vasculogenic mimicry is a unique process through which tumor cells imitate normal vascular endothelial cells to secure access to the blood flow. In this review, we consider molecular mechanisms underlying this phenomenon and its importance in the context of solid tumor development. We have analyzed survival strategies of tumor cells using vasculogenic mimicry and described potential therapeutic approaches aimed at tumor growth and metastasis suppression. Highlighting the methods of histological and molecular identification of vasculogenic mimicry promotes better understanding of this phenomenon and its early diagnosis. The review focuses on the necessity of further research in the area of vasculogenic mimicry to conceptualize mechanisms underlying carcinogenesis. We have analyzed 109 articles from the leading biomedical databases including SciVerse Scopus, PubMed, Web of Science and RSCI (Russian Science Citation Index) which allowed us to summarize current scientific data and identify the key trends in the area of molecular oncology.